The actual star : a novel - Byrne, Monica, 1981- (Harper Voyager, an imprint of HarperCollinsPublishers, 2021)
Through the epic saga of three reincarnated souls, this book takes readers on a journey over thousands of years and six continents where it demonstrates the entanglements of tradition and progress, sister and stranger, love and hate.